The Competition Neutrality in Malaysia: Challenges and Policy Options / Angayar Kanni Ramaiah - Kanni Ramaiah, Angayar (Faculty of Business and Management ; UiTM Press, 2018)
Competition law (CL) prevents anti-competitive conducts but does not ensure fair competition or level playing field with respect to State-Owned enterprises (SOEs). Hence, the principle of competitive neutrality promotes that government related business activities in competition with the private sector should not have a competitive advantage or disadvantage simply by virtue of government ownership and control (UNCTAD). Therefore, specific policies and legal rules is essential for achieving competitive neutrality. The Malaysian, Competition Act 2010 (CA2010) subjectively restricts and excludes some government linked enterprises. However, the some economic or, legal policy and political reasons limits CLs applicability and dictates its scope subjectively. In these context exemptions, de facto or de jure, direct or indirect state aid and restrictive licensing requirements impairs competition to benefit the domestic economy or national champion. This practice impacts the true spirit of market competition among rivals. Although Malaysian SOEs recognised as government’s toolbox for societal and public value creation but its future should to be more actively owned and managed to avoid competing unfairly on enterprises that can deliver more efficiently and effectively the goods and services that citizens need and want. In this context, three principal questions from the international trade perspective is analysed on (1) How important is state ownership within Malaysian context (2) What types of advantages should be granted to SOEs (or disadvantages afflicting them) and (3) What policies required to enhance effective competition among all market participants? The paper reviews the state of SOE with respect to exemptions and exclusions policy with respect to governance, independent decision-making, accountability and disclosure policy to improvise the level playing scope between SOE and private sector within the competition law perspective in Malaysia.